THE EFFECT OF ARTIFICIAL INTELLIGENCE–BASED LEARNING TOOLS ON STUDENT ACHIEVEMENT AND LEARNING ENGAGEMENT IN K–12 EDUCATION - Syahrani Syahrani; Hardi Tambunan; Firman Pangaribuan (Penelitian dan Pengembangan Ilmu, 2025)
This study evaluates the impact of Artificial Intelligence (AI)-based adaptive learning tools on student achievement and learning engagement at SMK Negeri 1 Percut Sei Tuan. Utilizing a quasi-experimental design, the research addresses the effectiveness of AI in suburban educational contexts characterized by specific infrastructure challenges and diverse digital literacy levels. The findings demonstrate that students utilizing AI-based tools achieved significantly higher academic performance compared to those instructed through conventional methods. Furthermore, a strong positive correlation was identified between learning engagement and academic success, suggesting that AI facilitates a more personalized and responsive learning environment. These results validate the application of Cognitive Load Theory and Self-Determination Theory in vocational education, proving that AI acts as a pedagogical catalyst that optimizes cognitive processes while fostering intrinsic motivation among students.